Intentions, motivations and obstacles toward entrepreneurships among UiTM Pahang final year students / Musramaini Mustapha … [et al.] - Mustapha, Musramaini; Mohamad, Siti Aishah; Azer, Ilyani; Jamal Abdul Nasir Lutfi, Siti Zubaidah; Mahmood, Wan Nurashikin (2012)
Nowadays, cultivating entrepreneurship has become a vital agenda in most countries. Entrepreneurship improves the standard of living among society by creating job opportunities and contributing to the development of our country. The Ministry of Higher Education collaborates with the Higher Learning Institutions have undertaken various programme to shape the minds and intentions of student's to become entrepreneurs. Nevertheless, according to Akpomi (2009), only 12.4 percent out of 100 would - be- graduate really aspire to become entrepreneurs after graduation. Due to that, it is crucial to investigate the level of intention and motivation to be an entrepreneur among our final year students. The sample of this study consists of UiTM Pahang 34 selected final year students from different course of study. The main objective of this paper is to explore better understanding on the intentional factors and motivational factors that could inspire students toward entrepreneurship. In order to capture the true scenario toward entrepreneurship among final year students. barriers also need to be considered. This study also investigates which obstacle becomes the major factor toward development of entrepreneurship among final year students. The finding from this research could provide information to the Ministry of Higher Education and the Higher Learning Institutions in order to realign Malaysia’s Universities graduates toward entrepreneurships